Design and development of a tabletop indoor planter box - Li, Junjing (Nanyang Technological University, 2022)
This report presents the design and development of a tabletop indoor planter box for vegetables as well as the hydroponics method used for this project. Due to the unpredictable weather conditions, growing high yield vegetables constantly can be a challenging task. Therefore, the aim of this project is to design a tabletop planter box that can grow vegetables indoor and to provide them with the required growing environment and conditions. By illustrating some issues faced by farming, and potential solutions, Hydroponics is shown to be a better choice. Hydroponic vegetables refer to vegetables produced by allowing the plant roots to come into direct contact with the nutrient solution. Hydroponics is an advanced cultivation method using soilless culture. The nutrient solution can replace the soil and provides the necessary growth factors for plants to grow normally and more efficiently, such as water and nutrients. Compared with the planter box in the current market, this project’s planter box is cheaper and lighter.